Antimicrobial and Anticancer Activities of Some Partially Acylated Thymidine Derivatives (Journal of Bio-Science, 2021)
The principal cause of human deaths in the world is primarily due to harmful pathogenic microbes as bacteria, a virus, and fungi. Searching for antimicrobial agents to prevent deaths with new structures and modes of action is an essential strategy of the research. Therefore, in the present study has been undertaken of thymidine and of its eleven acylated derivatives were employed as test chemicals for in vitro antibacterial evaluation against five human pathogenic bacteria. The compounds were also screened for antifungal functionality tests against two phytopathogenic fungi. It was observed that a good number of tested compounds exhibited moderate to good antimicrobial activities. It was also observed that these acylated compounds were more effective against the phytopathogenic fungi than those of the bacterial strains. Encouragingly, several tested chemicals showed better antibacterial and antifungal activities than the standard antibiotics employed. The minimum inhibition concentration (MIC) values of the compounds 3 (5´-O-butyrylthymidine), 7 (5´-O-palmitoylthymidine) and 12 (5´-O-4- dichloroacetylthymidine) were found to be 0.32 mg/ml and minimum bactericidal concentrations (MBC) values were found to be 0.63 mg /ml in each case. On the other hand, the minimum fungal concentration (MFC) was found to be (1.25 mg/ml) in the case of compound 7 (i.e., palmitoyl derivative) which may be used as antifungal active drug providing further investigation. In vitro MTT assays revealed that compounds 4 (5´-O-hexanoylthymidine) and 7 (5´-O-palmitoylthymidine) were effective against Ehrlich’s ascites carcinoma (EAC) cells and IC50 values were found to be 920.88 μg/ml and 792.90 μg/ml, respectively. So these compounds may be targeted for future studies for their usage as broad-spectrum antibiotics.J. Bio-Sci. 29(1): 11-22, 2021 (June)